Land cover changes in Bandar Lampung City, Indonesia 2016-2021 - Miswar, Dedy; Suyatna, Agus; Wan Abbas Zakaria; Wahono, Endro P.; Salsabilla, Annisa; Mubarok, Robby Anzilni; Yazid Saleh; Suhendro (Penerbit Universiti Kebangsaan Malaysia, 2023)
Land cover changes are a persistent occurrence in both urban and rural areas, currently deemed inevitable. This study delves into the transformations in land cover within Bandar Lampung City from 2016 to 2021, employing Geographic Information Systems (GIS) and remote sensing techniques. The data were procured through documentation, field surveys, and interpretation of Landsat 8 imagery using the maximum likelihood classification method. Encompassing the entire span of Bandar Lampung City between 2016 and 2021, the study site was subjected to a comprehensive analysis. The technique for sample selection employed purposive sampling, encompassing a total of 60 ground checkpoints for land cover assessment in both 2016 and 2021. The process of data collection encompassed observation, documentation, and subsequent analysis. This analysis entailed image interpretation through image analysis, spatial assessment, and descriptive analysis. The study's results revealed land cover changes in Bandar Lampung from 2016 to 2021, with the most significant changes occurring in vegetated and built-up areas, totaling 12.361 km2. Meanwhile, the land type that underwent the most significant alteration was vegetated land, experiencing a reduction in area by 6.813 km2. Vacant land exhibited the least change, with an additional area of 2.345 km2. This research holds significant implications for local governments in devising future plans that align with the prevailing trends in urban development. The findings can serve as a reference model for enhancing urban spatial planning.